Social innovation and service delivery in Belgium and South Africa. Issue 2 (20th May 2019) - Biljohn, Maréve Inge; Lues, Liezel
Abstract : Purpose: Social innovation (SI) remains a latent area in the South African local government (LG) sphere despite its growing use in public-sector service delivery globally. This paper aims to investigate the use of SI in the service delivery of LG through a comparison between the City of Ghent (CoG) (Belgium) and the Mangaung Metropolitan Municipality (MMM) (South Africa). Design/methodology/approach: Through a comparative case study approach, qualitative research methods were used to both collect and analyze the data. Data collection instruments included document analysis (naturally occurring data), semi-structured interviews (generated data) and focus group discussions (generated data). Findings: Although LG is obliged to collaborate with citizens, various factors influence citizens' ability to make contributions, even when platforms are created. Collaborative initiatives aid in the realization of collective development visions and enhance citizen participation in a more responsive and inclusive approach to service delivery. Collaborations would require citizens and LG officials to be empowered by finding new ways of working together, as well as developing skills. Practical implications: Citizens' participation when SI is used to enhance service delivery should be meticulously planned. Co-producing services require a conducive internal organizational context that advances citizen participation in the governance and decision-making of service delivery, which is likewise optimal for enhancing the use of SI during the respective co-production service delivery stages. Achieving a conducive internal organizational context is influenced by the role of LG officials and politicians in understanding the value proposition of participation in service delivery to citizens. This value proposition is crucial to building and establishing a trust relationship between citizens, LG officials and politicians. Finally, consensus concerning the concept of SI and its use and implementation is important to ensure its consistent use and application by a municipality, and thus calls for further in-depth investigation. Originality/value: SI is a nascent area for which the discourse is still under development, and it is a concept that is often the subject of debate in literature. This paper is justified by the fact that the use of SI in the South African LG sphere lags behind the growing use thereof in public-sector service delivery by LGs globally. In addition, the study presents novel insights regarding similarities and differences in the use of SI through a comparison between two LGs, namely, the MMM and the CoG.